174k views
5 votes
What is the solution for this equation? 3x - 1 = 5x - 11

User Fasseg
by
6.3k points

2 Answers

1 vote
Hi there.

3x - 1 = 5x - 11; get the variables to the same side, so subtract 3x from both sides.

2x - 11 = -1; add 11 to both sides to isolate our variable.

2x = 10; divide both sides by 2 to solve for our variable.

x = 5 is your answer.

I hope this helps!
User Rahul Sondarva
by
6.2k points
3 votes
3x - 1 = 5x - 11
Add 1 to both sides.
3x = 5x - 10
Subtract 5x from both sides.
-2x = -10
Divide by -2.

x = 5
User Super
by
5.7k points